2013
DOI: 10.4238/2013.february.28.5
|View full text |Cite
|
Sign up to set email alerts
|

Structure and immune expression analysis of hemoglobin genes from the blood clam Tegillarca granosa

Abstract: ABSTRACT. Hemoglobin (Hb) is the major protein component of erythrocytes in animals with red blood, although it can serve additional functions beyond the transport of oxygen. The blood clam (Tegillarca granosa) is one of the few mollusks that has Hb, although the structure and function of molluskan Hbs remain unclear. We characterized two unique and highly compartmentalized blood clam hemoglobin genes, Tg-HbIIA and Tg-HbIIB, at the molecular level. The full-length cDNA of Tg-HbIIA was 731 bp with a 450-bp open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…compared to the control groups. Differential temporal expression patterns of T. granosa HbII-A and -B genes in hemocytes were also detected in the presence of microbial ligands (LPS and PGN) and intact bacteria [140, 141]. Over 20 individual nucleotide polymorphisms have been identified across all three T. granosa Hb genes [141].…”
Section: An Emerging Role For Invertebrate (Bivalve) Hemoglobin In Inmentioning
confidence: 99%
“…compared to the control groups. Differential temporal expression patterns of T. granosa HbII-A and -B genes in hemocytes were also detected in the presence of microbial ligands (LPS and PGN) and intact bacteria [140, 141]. Over 20 individual nucleotide polymorphisms have been identified across all three T. granosa Hb genes [141].…”
Section: An Emerging Role For Invertebrate (Bivalve) Hemoglobin In Inmentioning
confidence: 99%
“…), a bivalve mollusk from the Arcidae family, is widely distributed on China’s east coast and in Southeast Asia [10]. It is a major fishery and aquaculture species with proteins, various vitamins and amino acids, resulting in its use in traditional Chinese medicine and seafood [11].…”
Section: Introductionmentioning
confidence: 99%
“…This sequencing has demonstrated that the majority of species examined most frequently have two to three Hb encoding genes. For example, Tegillarca granosa contains three different Hb genes; α and β encoding genes of the tetrameric Hb and a minor globin gene encoding the homo-dimeric Hb (Bao et al, 2013a). S.inaequivalvis also expresses three homologous Hb genes (α, β and minor) (Piro et al, 1996;Piro et al, 1998).…”
Section: Haemoglobins In the Family Arcidae Pteriomorphia Subclassmentioning
confidence: 99%
“…It is now widely accepted that invertebrate Hbs are understudied, particularly in reference to their evolution, distribution and functions (Alyakrinskaya, 2002;Bao et al, 2013a). In an attempt to address this knowledge gap, a quantitative investigation of Hb encoding genes was performed across five different tissues in A. trapezia individuals undergoing aerial exposure.…”
Section: Tissue Specific Expression and Neofunctionalisationmentioning
confidence: 99%
See 1 more Smart Citation